A prospective, observational study of patients with uncommon distal symmetric painful small-fiber neuropathy. - Jung-Lung Hsu (PLoS ONE, 2017)
To investigate the clinical characteristics of patients with uncommon distal symmetric painful small-fiber neuropathy (DSPSFN).From September 2012 to September 2014, participants between 18-70 years of age that had DSPSFN defined by clinical signs/symptoms and ID pain > 2 or DN4 > 4 on questionnaires for more than 1 month were included. Participants who had previous historical or laboratory evidence of common etiologies of DSPSFN were excluded. Enzyme activity and genetic studies for Fabry diseaseand familial amyloid polyneuropathy were performed after participants fulfilled the inclusion and exclusion criteria. The cryoglobulin test, autoantibodies studies and electrophysiological studies were performed in these participants.In total, 100 cases were enrolled in the current study. Three cases of subclinical diabetes mellitus and two cases of fibromyalgia were found. Fabry disease (1%) and familial amyloid polyneuropathy (3%) with Ala97Ser transthyretin (TTR) mutations were also detected. The cryoglobulin test was positive in 30% of participants, and these participants had higher DN4 scores than the negative group. In the autoantibodies studies, 59% of the participants had abnormal anti-Ro/SSA and/or anti-La/SSB antibodies.Cryoglobulinemia is not a rare etiology of uncommon DSPSFN. The long-term prognosis is quite good in these participants. From our structuralized protocol, Fabry disease and familial amyloid polyneuropathy could be easily detected in these cases of uncommon DSPSFN.